Polyphenol Consumption on Human Bile Acids Metabolism: Preliminary Data of Bile Acid Profiles in Human Biological Samples (P06-131-19) - Zhao, Anqi (Curr Dev Nutr, 2019)
OBJECTIVES: Bile acids (BAs) play a critical role in regulating human health through the activation of BAs receptor farnesoid X receptor (FXR) and membrane G protein coupled bile acid receptor-1 (TGR5). We aimed to develop methods to characterize BAs and their metabolites in human biological samples and characterize changes in BAs profile after chronic polyphenol consumption to help guide investigations on the potential health effects of polyphenols via BAs metabolism. METHODS: Plasma, fecal and urine samples from two human studies that included berry intake were used for developing qualitative analysis of BAs using ultra high-performance liquid chromatography (UHPLC) coupled with electrospray ionization quadrupole time of flight (QTOF). The compounds were identified based on the exact mass, fragmentation pattern, available reference standards and database search. To investigate the effect of chronic polyphenol consumption on BAs composition, pooled plasma samples (fasting and postprandial 2 h, n = 6) from a chronic (45 and 90 days) strawberry supplementation study (24 g freeze dried/day) with an older population were analyzed. RESULTS: Among 106 BAs and their metabolites which were tentatively identified in the samples used for method development, 70, 55, and 47 BAs species were characterized in plasma, feces and urine samples, respectively. The qualitative analysis of BAs in plasma samples from subjects following the strawberry consumption protocol detected 8 primary and 31 secondary BAs. After 90-days strawberry supplementation, two secondary BAs–glycolithocholic acid and 9(11), (5β)-cholenic acid-3α, 12α-diol were decreased to undetectable levels in the pooled fasting sample and the FRX/TGR5 agonists, including chenodeoxycholic acid, deoxycholic acid, cholic acid, glycodeoxycholic acid and taurocholic acid, showed increasing peak areas at 2 h postprandial compared to fasting. CONCLUSIONS: The changes in BAs profiles in fasting and postprandial plasma samples after chronic strawberry feeding suggest that strawberry polyphenols may alter BAs metabolism and the FXR/TGR5 signaling. FUNDING SOURCES: This work was funded by the California Strawberry Commission, USDA Intramural Funds and various donor funds to the Center for Nutrition Research, IIT.